The importance of the economic relationship between Canada and the U.S. - Suprun, Stepan; Bolotov, Ilya; Čajka, Radek, 1983-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2019)
This thesis aims at exploring the economic relationship between Canada and the U.S., and tries to identify key areas in the mutual relations, which play a significant role in keeping this relationship solid, but also cause some disruptions. Eventually, this paper should give an answer to the question: "Which country is more dependent on the mutual economic relationship?" The contents of this thesis are:-Development of the bilateral relations-Mutual economic relationship-Current problems and perspectives.
Vedoucí práce: Ilya Bolotov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses